2021
DOI: 10.1038/s41598-021-82067-w
|View full text |Cite
|
Sign up to set email alerts
|

Calcium calmodulin kinase II activity is required for cartilage homeostasis in osteoarthritis

Abstract: WNT ligands can activate several signalling cascades of pivotal importance during development and regenerative processes. Their de-regulation has been associated with the onset of different diseases. Here we investigated the role of the WNT/Calcium Calmodulin Kinase II (CaMKII) pathway in osteoarthritis. We identified Heme Oxygenase I (HMOX1) and Sox-9 as specific markers of the WNT/CaMKII signalling in articular chondrocytes through a microarray analysis. We showed that the expression of the activated form of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…The specific mechanisms involved in TRPV4 enhancement of chondrogenesis remain to be determined. Previous studies suggest that activation of TRPV4 drives expression of Sox9 via Ca 2+ /calmodulin signaling, 10 which is known to play a role in cartilage homeostasis and interact with the TGF‐β pathway 43,44 . TGF‐β and TRPV4 signaling pathways demonstrate synergistic transcriptomic profiles, including targets of SMAD3, JUN, and SP1, while also displaying Ca 2+ /calmodulin‐dependence 44 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The specific mechanisms involved in TRPV4 enhancement of chondrogenesis remain to be determined. Previous studies suggest that activation of TRPV4 drives expression of Sox9 via Ca 2+ /calmodulin signaling, 10 which is known to play a role in cartilage homeostasis and interact with the TGF‐β pathway 43,44 . TGF‐β and TRPV4 signaling pathways demonstrate synergistic transcriptomic profiles, including targets of SMAD3, JUN, and SP1, while also displaying Ca 2+ /calmodulin‐dependence 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggest that activation of TRPV4 drives expression of Sox9 via Ca 2+ /calmodulin signaling, 10 which is known to play a role in cartilage homeostasis and interact with the TGF-β pathway. 43,44 TGF-β and TRPV4 signaling pathways demonstrate synergistic transcriptomic profiles, including targets of SMAD3, JUN, and SP1, while also displaying Ca 2+ /calmodulindependence. 44 Together with our results, these findings depict TRPV4 as an active member in chondrogenic development, where it directly drives chondrogenic gene expression, including Sox9, by Ca 2+ /calmodulin-transduced interaction with the TGF-β pathway.…”
Section: Discussionmentioning
confidence: 99%
“…49,50 Several studies showed that CaMKII is activated in OA, both in human and in animal models of the disease. 51,52 We have recently shown that pharmacological blockade of CaMKII can exacerbate cartilage damage in a murine model of OA. 51 This is in keeping with a recent in vitro study showing that inhibition of CaMKII can decrease the anabolic activity of bone morphogenetic proteins 2 and 4 on the synthesis of ECM components in isolated chondrocytes 53 but it is in contrast with previous work from the Saito's group showing that CaMKII can promote OA development in mice via activation of the Hes1 transcription factor.…”
Section: Independent Signalling Network In the Acmentioning
confidence: 99%
“…55 Our more recent data further validated this hypothesis by showing that while the Wnt/CaMKII pathway is also upregulated in OA in vivo, its pharmacological inhibition exacerbated cartilage degradation in a murine model of the disease. 51 Wnt3a has been shown to mediate the simultaneous activation of βcatenin-dependent and Ca 2+ -dependent pathways in other biological systems 24,56,57 which have been shown to be reciprocally regulatory. 58 Separately, we showed that Wnt16 also shares the ability of mediating multiple and contrasting signals in the cartilage.…”
Section: β-Catenin-dependent and -Independent Pathways: A Matter Of B...mentioning
confidence: 99%
See 1 more Smart Citation